2020
DOI: 10.3390/geriatrics5040085
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Morbidity and Polypharmacy in Older People: Challenges and Opportunities for Clinical Practice

Abstract: Multi-morbidity and polypharmacy are common in older people and pose a challenge for health and social care systems, especially in the context of global population ageing. They are complex and interrelated concepts in the care of older people that require early detection and patient-centred shared decision making underpinned by multi-disciplinary team-led comprehensive geriatric assessment (CGA) across all health and social care settings. Personalised care plans need to remain responsive and adaptable to the n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
55
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 63 publications
2
55
0
2
Order By: Relevance
“…Where two or more health conditions coexist in this way, medical and social care needs are greater. This results in higher levels of service utilisation and costs [ 2 ] to a wide range of health and social care providers [ 3 , 4 ], for example, those living with MLTC have higher rates of unplanned hospital admission, longer durations of hospitalisation, require higher rates of polypharmacy and are more likely to be affected by adverse drug reactions [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Where two or more health conditions coexist in this way, medical and social care needs are greater. This results in higher levels of service utilisation and costs [ 2 ] to a wide range of health and social care providers [ 3 , 4 ], for example, those living with MLTC have higher rates of unplanned hospital admission, longer durations of hospitalisation, require higher rates of polypharmacy and are more likely to be affected by adverse drug reactions [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Older people presenting to secondary care with hip fracture are likely to be osteoporotic, sarcopenic, and also have several markers of frailty. As such their assessment and management should be multidisciplinary (orthopaedic, older people’s specialist teams, pharmacy, therapy, nursing, mental health, dietetics, speech and language) and be driven by the process of comprehensive geriatric assessment (CGA) [ 69 ]. Whilst this is the gold standard for patients presenting with a hip fracture, for less frail and more ambulant individuals presenting with other fragility fractures, i.e., wrist, shoulder and vertebral, fracture liaison services (FLS), which are typically multidisciplinary co-ordinated models of care systematically assess, identify and advise on risk factor management.…”
Section: Osteoporosis: Diagnosis and Managementmentioning
confidence: 99%
“…In this regard, fracture risk undoubtedly increases commensurate with the incidence of dementia. CGA for such patients may just identify achievable goals to attain in the short and medium term when risks and benefits of treatment are considered in context of the wider social, physical and psychological domains [ 69 ].…”
Section: Osteoporosis: Diagnosis and Managementmentioning
confidence: 99%
“…With increasing polypharmacy again, the risk for the occurrence of drug interactions increases inevitably and could thus lead to multiple unwanted side effects for the patient. A review in 2020 indicated that multimorbidity and polypharmacy are associated with a progressive loss of resilience and impaired homeostasis contributing to a significant burden on health and social care [ 10 ]. Furthermore, a retrospective, single-centre study in 2017 revealed that patients with potential inappropriate discharge medications showed an increased risk for readmission [ 11 ].…”
Section: Introductionmentioning
confidence: 99%